Mice lacking α1,3-fucosyltransferase 9 exhibit modulation of in vivo immune responses against pathogens - Kashiwazaki, Hiromi; Kakizaki, Masatoshi; Ikehara, Yuzuru; Togayachi, Akira; Narimatsu, Hisashi; Watanabe, Rihito (Pathology international, 2014)
Carbohydrate structures, including Lewis X (Lex), which is not synthesized in mutant mice that lack α1,3‐fucosyltransferase 9 (Fut9−/−), are involved in cell–cell recognition and inflammation. However, immunological alteration in Fut9−/− mice has not been studied. Thus, the inflammatory response of Fut9−/− mice was examined using the highly neurovirulent mouse hepatitis virus (MHV) JHMV srr7 strain. Pathological study revealed that inflammation induced in the brains of Fut9−/− mice after infection was more extensive compared with that of wild‐type mice, although viral titers obtained from the brains of mutant mice were lower than those of wild‐type mice. Furthermore, the reduction in cell numbers in the spleens of wild‐type mice after infection was not observed in the infected Fut9−/− mice. Although there were no clear differences in the levels of cytokines examined in the brains between Fut9−/− and wild‐type mice except for interferon‐β (IFN‐β) expression, some of those in the spleens, including interferon‐γ (IFN‐γ), interleukin‐6 (IL‐6), and monocyte chemoattractant protein‐1 (MCP‐1), showed higher levels in Fut9−/− than in wild‐type mice. Furthermore, Fut9−/− mice were refractory to the in vivo inoculation of endotoxin (LPS) compared with wild‐type mice. These results indicate that Lex structures are involved in host responses against viral or bacterial challenges.